Y-Chromosome Short Tandem Repeats: A Review - Christo S. Cherian; Mansi Mishra; Kajol Bhati (Indian Journal of Forensic Medicine and Pathology, 2025)
Since the early 1990s, the effective development of forensic Y-chromosome examination has led to its widespread use as a standard procedure in labs handling cases involving crime worldwide. The Y-chromosome is a powerful tool in forensic genetics since it can spot the masculine DNA through the most likely to vary genomic sequence the so called STRs. These sequences could be considered to be an irreplaceable asset to the generally worldwide used array of non-sex chromosomal loci used in the study of genetics with respect to forensics. The focus on the masculine part of the chromosome makes it speci𿿿cally of huge regardincases of the lumping up of feminine and masculine cell, such as in scenarios of de𿿿lement in sexual aspect. However, single set stature of chromosome andthefather to son passover of the masculine genetic material can make the detection and study of the short tandem repeats spotted on the male chromosomal gene dif𿿿cult when males have the exact same Y-chromosomal make up for nnumber of generations. This may complicate the very understanding of the fact that whether a DNA pro𿿿le belongs to a suspect or a paternal relative. On the other hand, Y-chromosome research can be used to study the very formation of a DNApro𿿿lein a given population which further enables us to study population genetics. As it is also evident that the people falling in the same patrilineal line generally do stay in the same place they were born indicating that there could not be much of a change in their culture and habitat, study of the masculine genetic material thus could be of great signi𿿿cance in understanding the habitat andcultureof an entire population. The study of forensic Y-chromosome analysis includes the disciplines of application of Y-genome haplotyping, the evaluation of outcomes, making a track of data of new projects and efforts. This𿿿eld has played ritical role in criminal investigations, and its continued development promises to bring even greater bene𿿿ts to forensic genetics.